2022
DOI: 10.3390/ijms24010474
|View full text |Cite
|
Sign up to set email alerts
|

TSLP as a Potential Therapy in the Treatment of CRLF2 B Cell Acute Lymphoblastic Leukemia

Abstract: Cytokine receptor-like factor 2 B-cell acute lymphoblastic leukemia (CRLF2 B-ALL) is a high-risk subtype characterized by CRLF2 overexpression with poor survival rates in children and adults. CRLF2 and interleukin-7 receptor alpha (IL-7Rα) form a receptor for the cytokine thymic stromal lymphopoietin (TSLP), which induces JAK/STAT and PI3K/AKT/mTOR pathway signals. Previous studies from our group showed that low TSLP doses increased STAT5, AKT, and S6 phosphorylation and contributed to CRLF2 B-ALL cell surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…CRLF2 overexpression has been widely confirmed to be associated with adverse outcomes in B cell acute lymphoblastic leukemia (B-ALL) [ 45 ]. It has been shown that high-dose of thymic stromal lymphopoietin (TSLP) can induce apoptosis, impeding the proliferation and migration of CRLF2 B-ALL tumor cells [ 46 ]. Furthermore, the synergistic combination of the JAK1/2 kinase inhibitor ruxolitinib with conventional treatment has demonstrated enhanced efficacy in CRLF2-altered B-ALL [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…CRLF2 overexpression has been widely confirmed to be associated with adverse outcomes in B cell acute lymphoblastic leukemia (B-ALL) [ 45 ]. It has been shown that high-dose of thymic stromal lymphopoietin (TSLP) can induce apoptosis, impeding the proliferation and migration of CRLF2 B-ALL tumor cells [ 46 ]. Furthermore, the synergistic combination of the JAK1/2 kinase inhibitor ruxolitinib with conventional treatment has demonstrated enhanced efficacy in CRLF2-altered B-ALL [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is important to underline that the sfTSLP is not only necessary for homeostasis, but it is also involved in carcinogenesis [ 1 , 29 , 36 ]. In human lung cancer, sfTSLP mRNA is significantly more expressed in the intratumoural tissue compared to the peritumoural area [ 37 ].…”
Section: Tslp Isoformsmentioning
confidence: 99%